URGENSI PENERAPAN SYARIAH DALAM BISNIS JASA KONSTRUKSI - Firmansyah, Kholis (Irtifaq, 2016)
In the case of national development, it is very necessary to involve construction service companies, because construction services have an important and strategic role, given the construction services produce the final product in the form of buildings or other physical forms, both in the form of infrastructure and facilities that support the growth and development of various fields. In the implementation of construction services business, the implementation of sharia is very urgent. Anything that causes the implementation of sharia becomes very urgent in the construction services business, partly due to the rise of unhealthy business culture in the business world of construction services where there is fraud, bribery and kong kalikong / agreement to do no good in the effort to get the project and the reduction of scales or dose in project implementation; as well as the efforts made by Muslim businessmen in eliminating the illicit elements in the business, namely eliminating the haram element in terms of capital by obtaining a kosher capital and non ribawi, eliminating the haram elements of how to get the project and eliminate the element of haram in the implementation of the project. So in that case the understanding of Islamic sharia and its implementation is needed in business-oriented happiness of the world and the hereafter.Keyword : Syari’ah Principle, Construction, riba